(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This study revisits the Whorfian hypothesis of linguistic relativity by examining the role of language in shaping temporal cognition and behavior. Drawing on both foundational theories by Benjamin Lee Whorf and empirical insights from contemporary neo-Whorfian scholarship, the research investigates how linguistic structures contribute to culturally specific perceptions of time. Through a comparative analysis of temporal metaphors in Mandarin and English, and an ethnopoetic examination of non-linear narrative patterns in Chol folktales, this paper highlights how language-bound conceptualizations influence both thought and social behavior. Utilizing Dell Hymes’ ethnopoetic model, the study uncovers how the organization of narrative discourse in the Chol language reflects unique temporal frameworks that resist linear sequencing. The synthesis of experimental and ethnographic data affirms the cognitive implications of linguistic diversity, arguing that language does not merely express but actively constructs temporal and behavioral schemata.